Factors Affecting Midwife Attitude and Practice in Providing Service during Covid-19 Pandemic in Cengkareng Regional General Hospital - Carolin, Bunga Tiara; Widowati, Retno; Siagian, Chory Pebrini (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This research was done analytically through cross-sectional approach. The sampling was done through total sampling obtaining 50 midwives. In order to obtain the research data, questionnaire was used, whose results were further analyzed using Chi-Square test. Univariate analysis obtained results regarding the distribution of age frequency among the respondents which were 20-35 years old (54%), working length was more than 5 years (60%), no comorbidity (56%), PPR completeness (52%), and knowledge (64%). Meanwhile, bivariate analysis discovered the effect of age (p=0.002) (p=0.002); working length (p=0.000) (p=0.001); comorbidity (p=0.000) (p=0.000); knowledge (p=0.000) (p=0.000); PPE completeness (p=0.001) (p=0.001) on midwives attitude and practice in providing service during COvid-19 pandemic in Cengkareng Regional General Hospital in 2021. Based on the research results, it was summed up that there is relationship between age, working length, comorbidity, knowledge, and PPE completeness with midwives attitude and practice in providing service during Covid-19 pandemic